أثر مكتبات المطالعة في تنمية مهارة القراءة لدى الأطفال (El-Wahat Journal for Research and Studies, 2021)
Reading Is The Mechanism That Allows Knowledge And Science To Be Received In Different Forms; They Are One Of The Few Means Of Acquiring Scientific Skills, And Thus They Are Of An Important Nature. Without Them,- In Any Case - To Communicate With Different Scientific Patterns, Such As The Book And The Magazine And The Department Of Knowledge And So On.Different Countries And Governments Have Given This Skill (Reading) The Utmost Importance; They Have Provided Public Reading Spaces, Including Specialized In A Particular Area Of Knowledge. The Interest Of Some Countries Has Been To Allocate Reading Spaces To Certain Segments Of Society, Because It Is Favored And High, Because A Child Today Is The Man Of Tomorrow.The Libraries Of Our Country Have A Great Deal Of Interest And Focus. Algeria Has Built Many Different Libraries, Including Municipal Libraries, Libraries Of Cultural And Youth Houses, Not To Mention School Libraries, Reading Rooms And Libraries In Our Universities; This Has Enriched And Developed Minds , And Developed By Receiving Different Methods Of Knowledge And Acquisitions.This Article Attempts To Explain The Role Played By The Public Reading Libraries In Algeria, Focusing On Their Impact On The Establishment Of The Child's Reading Culture, And Its Role In The Promotion And Promotion Of Reading And Literary Products Among Them, And The Development Of This Skill, Which Is No Less Important Than Other Language Skills Other (Listening, Speaking And Writing).